Dust provenance and its role as a potential fertilizing agent for the Okavango Delta, Botswana. Issue 8 (11th March 2020) - Humphries, Marc S.; Benitez‐Nelson, Claudia R.; Bizimis, Michael; Ralph, Timothy J.; Larkin, Zacchary T.; McCarthy, Terence S.
Abstract: Dust plays a globally important role in supplying biologically essential elements to landscapes underlain by nutrient‐poor substrates. Here we show that dust may play a significant role in sustaining productivity in the vast wetlands of the Okavango Delta in southern Africa, one of the world's richest biodiversity hotspots. Dust accumulates preferentially on tree‐covered islands in the seasonal swamps of the Delta, creating pockets of fine‐grained, nutrient‐rich material within the semi‐arid landscape of the Kalahari Desert. Strontium and neodymium isotopes reveal that this dust likely originates predominantly from the Makgadikgadi salt pans, located 300 km away, and contributes 10–80% of the fine‐grained material present in Okavango island soils. Surface material sourced from the Makgadikgadi Pans contains relatively high amounts of bioavailable phosphorus and iron, potentially influencing Okavango Delta biological productivity. We propose that long‐term ecosystem productivity and nutrient availability in the Okavango may be strongly mediated by regional dust inputs. Understanding the influence of dust deposition on nutrient loads and biogeochemical cycling is thus critical for predicting the response of the Okavango Delta to future changes in climate. We suggest that dust inputs may play a significant role in the supply of nutrients to other large, global wetland systems located in dryland environments. © 2020 John Wiley & Sons, Ltd Abstract : We show that dust is an important contributor to the vast Okavango Delta ecosystem. Isotope compositions reveal that dust is likely sourced from the Makgadikgadi Pans. The aeolian supply of bioavailable P and Fe may play a role in ecosystem productivity.